One size does not fit all: an exploratory interview study on how translational researchers navigate the current academic reward system - Kools, Farah R. W.; Fox, Christine M.; Prakken, Berent J.; van Rijen, Harold V. M. (Frontiers in Medicine, 2023)
Introduction: Translational research is a subfield of the biomedical life sciences that focuses on clinically driven healthcare innovations. The workforce of this subfield, i.e., translational researchers, are diversely specialized and collaborate with a multitude of stakeholders from diverse disciplines in and outside academia in order to navigate the complex path of translating unmet clinical needs into research questions and ultimately into advancements for patient care. Translational researchers have varying responsibilities in the clinical, educational, and research domains requiring them to split their time two- or three-ways. Working between these domains and alongside peers who do not split their time as such, raises questions about the academic reward system used to recognize their performance, which mainly focuses on publication metrics within the research domain. What is unclear is how combining research tasks with tasks in the clinical and/or educational domains effects translational researchers and how they navigate the academic reward system. Methods: In this exploratory interview study, semi-structured interviews were conducted to gain a deeper understanding of the current academic reward system for translational researchers. Stratified purposeful sampling was used to recruit fourteen translational researchers from varying countries, subspecialties, and career stages. The interviews were coded after data collection was complete and arranged into three overarching result categories: intrinsic motivation, extrinsic factors, and ideal academic reward system and advice. Results: We found that these fourteen translational researchers were intrinsically motivated to achieve their translational goals while working in settings where clinical work was reported to take priority over teaching which in turn took priority over time for research. However, it is the latter that was explained to be essential in the academic reward system which currently measures scientific impact largely based on publications metrics. Conclusion: In this study, translational researchers were asked about their thoughts regarding the current academic reward system for translational research. Participants shared possible structural improvements and ideas for specialized support on an individual, institutional, and also international level. Their recommendations focused on acknowledging all aspects of their work and led to the conclusion that traditional quantitative academic reward metrics do not fully align with their translational goals.